אירוניה וחסד: הערה על קולו של סמי ברדוגו - הירשפלד, אריאל (מכאן, 2017)
This essay deals with two main modes in Berdugo's prose – the ironic gaze and the voice of grace and compassion. An analysis of two early short stories by Berdugo shows the immanent connection between these modes and the role of two kinds of symbiosis that create them: the symbiotic relationship between a child and his mother in "Shouk" creates the voice of compassion, and the profound relationship between a boy and his ailing and dying father in "Flard" are the origin for the sharp and complex ironic mode in Berdugo's writing.